Middle managers competencies in higher technical education institution: a systematic review / Mohammad Al Bukhari Marzuki - Marzuki, Mohammad Al Bukhari (Universiti Teknologi MARA, 2021)
Numerous research studies have been conducted on middle leadership in higher education. However, research on middle leadership competencies in the context of higher technical education is relatively rare. As such, the objective of this paper is to undertake a comprehensive evaluation of the existing academic research on middle leader competencies. This study used a systematic literature review methodology to rigorously synthesis research, identifying a total of 721 articles in the first stage and synthesizing a final sample of six research papers. The synthesis of the findings in this SLR on the middle leader's competencies revealed a dearth of research on middle leader's technical and personal competencies; a scarcity of studies on middle leader's technical and personal competencies; and a predominance of competencies discussed leaning toward the general competencies of middle leaders in higher education institutions. Future study should examine the impact of middle leader capabilities on the efficacy of managing respective units or departments, as well as the significance of middle leader technical competencies in a particular field.